Parameters of social existence and social functioning of lesbians: Lesbian body in processes of social interactions - Mršević Zorica Ž. (Temida)
Analysis of characteristics of a lesbian body in processes of social interaction is a method of analysis social relations of lesbians, their relationships with the heterosexual world and revealing specific lesbian practices, outlooks, habits and customs, behavior and general characteristics of lesbian sub culture. Making somebody different than a "normal human", meaning less human, is the main way of making the whole group target of justified discrimination, violence and hate crime. Therefore, providing understanding of differences provides a ground for personal, political and legal sensitivity, understanding and tolerance towards both the "otherness" and the "others".